10-year Portuguese football strategic plan: sustainable growth - Santos, Gonçalo Ferro (2022)
This analysis serves as a complement to the 10-year Portuguese Football Strategic Plan conducted jointly with Federação Portuguesa de Futebol and Deloitte. After measuring the impact of fan engagement, women’s football, academic football, broadcasting rights, and international exposure, this report was directed towards the emerging rise of the gaming and eSports industry. This analysis aims to understand what has already been implemented across different sports concerning technology and how Portuguese football can incorporate different innovations. The goal is to increase both the number of fans and their experience when consuming football in Portugal.